Religion and Change Fourth Annual Conference 2021 - Grosshans, Hans-Peter (European Academy of Religion (EuARe) Lectures, 2023)
Are religions like everything else in the world, subject to permanent change? Or are they perhaps the only stable element for people in a world of permanent change? Within the wide field of this discourse, five authors - Rowan Williams, Judith Wolfe, Guy G. Stroumsa, Vassilis Saroglou and Azza Karam - illuminate the relation of religion and change in its diverse aspects.